1968
DOI: 10.1063/1.1670289
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Study of the Adsorption of Methanol and Ethanol on Magnesium Oxide

Abstract: The adsorbed species which result when magnesia is exposed to methanol or ethanol vapor are reported. Five different surface species have been identified for both methanol and ethanol. At 25°C a tightly bound layer of liquid alcohol is observed. When this is removed by heat and evacuation, another species appears which is identified as a surface methoxide in the case of methanol and ethoxide in the case of ethanol. When the magnesia sample is heated to 165°C in alcohol vapor, a formatelike surface compound is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…The new OH group that formed from the dissociative adsorption gave rise to broad bands near 3600 cm À1 . When the adsorption temperature reached 393 K, new bands appeared at 1599 and 1394 cm À1 , these could be ascribed to the transformation of methoxide species into formate ions [19,20]. However, for methanol adsorbed on CaO (see Fig.…”
Section: Methanol Adsorption and Desorption On Mgomentioning
confidence: 99%
“…The new OH group that formed from the dissociative adsorption gave rise to broad bands near 3600 cm À1 . When the adsorption temperature reached 393 K, new bands appeared at 1599 and 1394 cm À1 , these could be ascribed to the transformation of methoxide species into formate ions [19,20]. However, for methanol adsorbed on CaO (see Fig.…”
Section: Methanol Adsorption and Desorption On Mgomentioning
confidence: 99%
“…This method precludes the use of solvents that may modify the surface structure of MgO samples [47]. Since the nanocubes exhibit h1 0 0i surfaces, the compression axis is expected to be parallel to [0 0 1].…”
Section: In Situ Tem Nanocompressionmentioning
confidence: 99%
“…Junko Kondo et al [23] reported similar results, which were attributed to two kinds of methoxide species. The new OH group formed from the dissociative adsorption gave rise to broad bands near 3500 cm −1 .When the adsorption temperature reaches 393 K, new bands appeared at 1599 and 1394 cm −1 , which could be ascribed to the transformation of methoxide species into formate ions [24,25]. Fig.…”
Section: Ftir Spectroscopy Of Absorbed Methanol and Methanol Tpsrmentioning
confidence: 99%